Environmental Ethics And Approaches To Civil Enforcement In Law Enforcement - Z.A. Abduazimova; Sh.A. Bahromova (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article analyzes the concept of environmental ethics and law and its foundations, the participation of environmental law in protecting the rights of citizens in its implementation, problems associated with the civil approach to environmental law and proposals for their solution, as well as its prospects and civil legal foundations. A comparative analysis of international experience and national legislation is carried out, and scientific conclusions are drawn on the development of civil approaches to environmental ethics and law enforcement.